Gerakan Stop Asian Hate: Media, Politik dan Teknologi dalam Melawan Diskriminasi - Budi Ayu, Dewi Pristya; Apriani, Kadek Dwita; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 2 No 2 (2023): Jurnal Ilmu Politik, 2023)
This article explores the dynamic interplay between media, politics, and technology within the context of the Stop Asian Hate movement. Fueled by rising discrimination and violence against Asian communities, this movement has harnessed the power of social media for awareness, challenged harmful media stereotypes, and driven legislative changes at various levels of government. It underscores the critical role of responsible media representation, political discourse, and technology-driven activism in the ongoing fight against discrimination and hate. While these elements have amplified the movement's impact, they also present challenges that demand collective efforts for a more inclusive society.